Letrozole treatment alters hippocampal gene expression in common marmosets (Callithrix jacchus) - Edwards, Mélise; Lam, Sam; Ranjan, Ravi; Pereira, Mariana; Babbitt, Courtney; Lacreuse, Agnès (Hormones and behavior, 2023)
Aromatase inhibitors (AIs) are a class of drugs commonly given to patients with estrogen receptor (ER)-dependent breast cancers to reduce estrogenic stimulation. However, AIs like Letrozole are associated with negative side effects such as cognitive deficits, sleep disturbances and hot flashes. We have previously shown that these negative effects can be recapitulated in common marmosets (Callithrix jacchus) treated with Letrozole (20 μg daily) for 4 weeks and that marmosets treated with Letrozole show increased levels of estradiol in the hippocampus (Gervais et al., 2019). In order to better understand the mechanisms through which AIs affect cognitive function and increase steroid levels in the hippocampus, we used bulk, paired-end RNA-sequencing to examine differentially expressed genes among Letrozole-treated (LET; n = 8) and vehicle-treated (VEH; n = 8) male and female animals. Gene ontology results show significant reduction across hundreds of categories, some of the most significant being inflammatory response, stress response, MHC Class II protein complex binding, T-cell activation, carbohydrate binding and signaling receptor binding in LET animals. GSEA results indicate that LET females, but not LET males, show enrichment for hormonal gene sets. Based on the transcriptional changes observed, we conclude that AIs may differentially affect the sexes in part due to processes mediated by the CYP-450 superfamily. Ongoing studies will further investigate the longitudinal effects of AIs on behavior and whether AIs increase the risk of stress-induced neurodegeneration. •Transcripts involved in immunity were downregulated in LET animals' hippocampus.•Letrozole upregulated transcripts in hippocampus involved in cell signaling.•Gene set testing revealed sex differences in Letrozole treatment.•Systemic aromatase inhibition may predispose patients to CNS impairment.